EVALUATION OF DYNAMIC PROPERTIES OF HIGH PERFORMANCE STEEL-FIBER CONCRETE BY USING NON-DESTRUCTIVE TESTS (Iraqi Journal of Civil Engineering, 2007)
Abstract: The presented investigation studies the effect of steel fiber content on the dynamic properties of High Performance Steel Fiber Concrete by using non-destructive testes; Vibration tests (Electrodynamics tests) were used to obtain the dynamic modulus of elasticity, dynamic shear modulus (modulus of rigidity), damping capacity, and dynamic Poisson‘s ratio. The results demonstrated in general an improvement in dynamic properties, which were tested for example, the percentage increasing in compressive strength relative to the reference concrete were 2.5%, 6.6%, 5.8% for High Performance Concrete (HPC) with 0.5%, 1%, and 1.5% steel fiber by volume of concrete respectively.